PENGARUH KOMPRES REBUSAN DAUN SIRIH MERAH TERHADAP PENURUNAN NYERI ARTRITIS REUMATOID PADA LANSIA DI KABUPATEN SIDENRENG RAPPANG - Dinah Aulia Habsan; nurdin, sulkifli; Fitriani (Universitas Sam Ratulangi, 2026)
Background: Rheumatoid arthritis is an autoimmune disease that causes chronic pain in the joints, especially in the elderly. One of the complementary therapies that can be used to reduce pain is red betel leaf decoction compress, which has anti-inflammatory and analgesic content. Objective: This study aims to determine the effect of red betel leaf (Piper crocatum) decoction compress on the pain level of rheumatoid arthritis in the elderly. Methods: This research was conducted on 20 January 2025-20 February 2025 in the UPT Puskesmas Lawawoi Work Area. This study used a pre-experimental design with a one-group pretest-posttest approach. The research sample totalled 17 respondents, who were selected using purposive sampling technique. Data were collected using a numerical pain scale and analysed using the Paired t-Test test to determine differences in pain levels before and after the intervention. Results: The results of the analysis showed that the average pain level before the intervention was 5.12, while after the intervention it decreased to 2.71. The results of the Paired t-Test test showed a value of p = 0.000 (p < 0.05), which means there is a significant difference between the pain levels before and after the intervention. Conclusion: Red betel leaf (Piper crocatum) decoction compress is effective in significantly reducing pain levels in elderly patients with rheumatoid arthritis. This complementary therapy can be considered as an alternative non-pharmacological intervention in pain management for the elderly. Keywords: Complementary therapy; pain; red betel leaf compress; rheumatoid arthritis.